A review of groundwater in islands using SWOT analysis - Praveena, Sarva Mangala; Aris, Ahmad Zaharin (Inderscience Enterprises, 2009)
This paper has focused and reviewed the groundwater of 55 islands around the world using Strength, Weakness, Opportunities and Threats (SWOT) analyses selected based on existing literatures and studies conducted. The SWOT analysis output fills in the gap of scientific knowledge and helps in groundwater management. The overall of groundwater management in islands should be conducted by the highest government level. The institutional framework must make sure that any development and management of water resources in these islands take place in national level planning. The main thing is to ensure collaborations between agencies for sustainable management of groundwater in islands.